The Second Violin Consert Of Bela Bartok In The Context Of Genre Development - Dzizinska, Nataliia (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2020)
Relevance of the study. One of the leading instrumental types of the concert is the violin concerto, presented in the first half of the twentieth century by almost 500 works. An important stage in the evolution of the genre during this period were the violin concertos by the outstanding Hungarian master Bela Bartok, which were firmly in the repertoire of modern performers. The second concerto (1938), dedicated to a friend of the composer, the famous Hungarian violinist Zoltán Székely, was first performed by him on May 29, 1939 in Amsterdam. Widely covered in musicological literature, however, it has not yet been considered in a genre context. Main objective(s) of the study is to find out the correspondence of Bartok’s Second Violin Concerto to the general trends in the development of the violin concerto in the first half of the 20th century and to reveal individual features of the interpretation of the genre. Methodology. In the course of the study, the following methods were used: historical – to trace the history of the development of the violin concert genre in the first half of the twentieth century; systemic – for grouping concerts of the time according to various parameters; comparative – to compare individual samples of the genre; structural-functional, intonational -dramatic, semantic – for a comprehensive analysis of the Second Violin Concerto of B. Bartok. The main results / findings and conclusions. The development trends of the violin concerto genre in the first half of the twentieth century, systematized for several parameters: stylistic features, compositional structure, imaginative concept and interpretation of the genre are considered. According to the specified parameters, the Second Violin Concerto of B. Bartok was analyzed, the correspondence of the revealed features of his organization to the main trends in the development of the violin genre was clarified, and the manifestation of individual features of his interpretation was emphasized. The circumstances of the creation of the Bartok concert are highlighted and the conditionality of the figurative concept of the work is proved. The patterns of musical dramaturgy were revealed by analyzing verbal remarks reflecting the leading figurative spheres: heroic (Risoluto), lyrical (Calmo) and scherz (Allegro scherzando). The compositional features of the concert are characterized, the updating of the three-part model typical of the genre is justified due to the introduction of the variational principle, operating at all levels of the organization of the whole. Identified folk influences in the style of Bartok’s violin concerto, in particular, the assimilation of the mode-intonational and rhythmic elements of the styles of parlando rubato and verbunkos. The interaction of solo and orchestral parts is traced; an expansion of the range of performing techniques of playing the violin is noted.